Registered Name or Business Fantasy: Corporate Communication in the Construction of Fantasy Sustainability - Ribeiro, Backer (2015)
The sustainability has become a fashion, and all business organisations want tobe fashionable. Everyone aims to trend and developed their items in a sustainableway, protecting human health. This article proposed a reflection due to the role played by business communication in its relation with sustainability, the work of social communicators and the challenges of planet preservation. We also introduce communication strategies developed by corporate media. To conclude, we present some cases which show how organisations perform their business and deny thier own communication.